Coupling study on dynamics and TEHL behavior of high-speed and heavy-load angular contact ball bearing with spinning. (August 2015) - Shi, Xiu-Jiang; Wang, Li-Qin; Mao, Yu-Ze; Qin, Fen-Qi
Abstract: In this paper, on the basis of quasi-dynamic theory and TEHL (thermal elastohydrodynamic lubrication) theory, a combined numerical algorithm is proposed to judge the lubrication state of high-speed and heavy-load angular contact ball bearing on aero-engine main-shaft. Based on the new coupled numerical model of bearing quasi-dynamics and TEHL analysis in point contacts, a whole coupled theoretical analysis of bearing lubricated problem is conducted from whole to local, results show that slide–roll ratios are closely related to spinning and gyration, the bearing stays in a full film state under normal operating conditions and the short-term poor lubrication may occur under the conditions of slowdown, start or stop. Highlights: We propose a combined numerical algorithm of bearing quasi-dynamics and TEHL analysis. We set up a coupled numerical model of bearing quasi-dynamics and TEHL analysis in point contacts. A whole theoretical lubricated analysis of ball bearing considering spinning is completed. The judgment and transition of lubrication state are obtained by combined algorithm.